Effects of the structural period variations and near field earthquakes on a fuzzy controller performance for the variably baffled tuned liquid damper - Mahdi Kiani; Hamed Enayati; Meisam Qorbani Fouladi (Numerical Methods in Civil Engineering)
Structural control as a countermeasure against unwanted structural vibrations is divided into three general categories known as passive, active, and semi-active. Among various structural control devices, the tuned Liquid Damper (TLD) can lend itself well to reducing structural demands through all of the control scenarios. In this paper, demands of Single degree of freedom (SDOF) structures subjected to near and far field ground motions are controlled by a recently developed TLD, named a variably baffled tuned liquid damper (VBTLD), through semi-active and passive control. The effects of the controlled structural period variations on the performance of the linear optimal control algorithm and a fuzzy controller have been examined comparatively. Results show that the semi-active fuzzy controller has better performance than the linear optimal control algorithm. The fuzzy controller can reduce both RMS and peak responses, effectively and its performance improves with increasing the controlled structural period. Furthermore, the fuzzy controller has the same controlling effects under near and far-field earthquakes.